Polymer material for optical devices application - Ibrahim, Mohd. Haniff; Mohd. Kassim, Norazan; Mohammad, Abu Bakar; Mohd. Supa'at, Abu Sahmah (IEEE, 2004)

(untitled)
In this paper, an overview of polymer material in optical waveguiding technology is presented. This include a review on the type of polymer being used worldwide in the development of optical devices, track record and performances of polymer based optical devices successfully being developed as compared to other optical materials and also on the external field control of the polymer material for active devices application. Further discussion will then include the current research in polymer based optical waveguiding technology held in our Photonic Research Group together with possible development and commercialization.